The great Irish famine and population: The long view - Guinnane, Timothy W. (American Economic Review, 1994)
This paper first sets the demographic consequences of the Great Famine in the context of Irelands long-term population history and then discusses what may be the most puzzling feature of Irish population history the demographic patterns that emerged during the second half of the 19th century. The paper focuses on rural Ireland where these changes were most stark. (EXCERPT)